The BR-163/MS and the links with the visible and invisible State: the “surface acts” of a road concession (consequence of the “political impeachment” (coup) in Brazil in 2016) (Research, Society and Development, 2021)
The BR-163/MS was privatized to CCR MSVia in March 2014 as part of the Logistics’ Investment Program (PIL). There were plans to invest R $ 3.5 billion in the project and the concessionaire was expected to expand the highway's operational capacity in five years. However, the coup in Brazil in 2016 and the rise of the Temer government changed all expectations and installed a chaotic process in the context of the privatization of BR-163, because the public resources that would be destined to make the works possible were interrupted. In this way, a series of political confrontations on the political scene (surface acts) began to occur between CCR MSVia (dominant social class), ANTT (state bureaucracy) and parliamentarians (reigning social class), confrontations that culminated in the BR- 163/MS. Therefore, the objective of this article is to verify the political contradictions surrounding the privatization process of BR-163 / MS, more specifically the “surface Acts” that led to the failure of the decentralization process. To this end, we used a bibliographic and documentary survey, as well as field work.